THE FINANCIAL FEASIBILITY ANALYSIS OF THE LAYER DUCK FARM WITH INTENSIVE MAINTENANCE SYSTEM (A Case of Study on A Layer Duck Farm in Banjarangkan Village, Klungkung Regency) - I M., Suprapta; Sukanata, I W.; Wiyana, I K. A. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
The purpose of this research was to know about the production management and the financial feasibility of the layer duck farms as well as its sensitivity to the increase of feed prices and the decrease of eggs prices. This reasearch was conducted on December 2016 until January 2017 atI Ketut Mendra’s layer duck farm in Banjar Selat,Banjarangkan Village, Klungkung. The located of the study have determined by purposive. The data used primary data and secondary data that analyzed by quantitative descriptive method which includes the analysis of investment criteria, payback period, breakeven point, and switching value.The results of this study indicate that I Ketut Mendra’s layer duck farm was financially feasible indicated by the positive Net Present Value (NPV) of Rp 82,315,887, Internal Rate of Return (IRR) of 27.37%, Net Benefit Cost Ratio (Net B/C) of 1.46. Pay Back Period and Break Even Point could be reached on 0.45 years dan 6.93 years respectively. BEP production of this farm was273,702eggs/year, while the BEP price wasRp. 1,433 per egg. This farm was very sensitive to the decrease of theeggs pricesand the increase of the feed prices with a value of 3.5% and 4.67% respectively.